2002
DOI: 10.1191/0267659102pf534cr
|View full text |Cite
|
Sign up to set email alerts
|

Coronary sinus rupture with retrograde cardioplegia

Abstract: Coronary sinus (CS) rupture occurring during retrograde cardioplegia (RCP) is a rare complication. Patients with left ventricular hypertrophy are at higher risk for injury to the CS. The patient was a 66-year-old female with hypertension, ischemic cardiomyopathy and dysrhythmias, who had evidence of an anterior wall myocardial infarction, congestive heart failure and angina. During coronary artery bypass surgery, antegrade cardioplegia was initially administered, but aortic insufficiency prevented adequate myo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…It is also possible that pericardial fluid collection and haematoma formation were related to CS injury in some of the cases. Contrary to RCVI studies, development of haematomas on the atrioventricular groove, pericardial fluid collections and damage to the CS have been reported in the field of cardiac surgery and have been related to traumatic catheter insertion, overinflation of the balloon in the CS and elevated CS infusion pressure during retrograde cardioplegia 27–30. With retrograde cardioplegia, the CS is accessed with a balloon-catheter to occlude the CS and subsequently infuse fluid to arrest the heart and protect the myocardium.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that pericardial fluid collection and haematoma formation were related to CS injury in some of the cases. Contrary to RCVI studies, development of haematomas on the atrioventricular groove, pericardial fluid collections and damage to the CS have been reported in the field of cardiac surgery and have been related to traumatic catheter insertion, overinflation of the balloon in the CS and elevated CS infusion pressure during retrograde cardioplegia 27–30. With retrograde cardioplegia, the CS is accessed with a balloon-catheter to occlude the CS and subsequently infuse fluid to arrest the heart and protect the myocardium.…”
Section: Discussionmentioning
confidence: 99%
“…Injuries to the coronary sinus have occurred with a wide variety of instruments, such as guidewires, angioplasty catheters, balloon inflation, and by surgeons directly placing coronary sinus catheters. 3,4 In addition to 2-D imaging, real-time 3-D echocardiography has been used to guide a variety of catheter-based cardiac interventions including atrial septal occlusion, mitral balloon valvuloplasty, ventricular septal defect closure, and others. 5 In this study, we present a case in which 3-D imaging facilitated placement of a percutaneous coronary sinus catheter.…”
Section: Discussionmentioning
confidence: 99%
“…CS rupture is extremely rare. Most of the reported cases in the scientific literature occurred during retrograde cardioplegia, with none resulted in patients' death . Sabzi et al in a retrospective analysis found female gender and low body mass index as potential predicting factors for CS rupture ; in their population the incidence for CS rupture was 1.02% (15 patients of 1,465).…”
Section: Discussionmentioning
confidence: 99%
“…Coronary sinus (CS) perforation is a very rare event, described as infrequent complication of certain cardiac surgery procedures, such as coronary sinus perfusion catheter placement for retrograde cardioplegia , or during CS lead implantation or extraction . Other few cases reported in literature are anecdotic, and even more rare .…”
Section: Introductionmentioning
confidence: 99%